2014
DOI: 10.1016/j.ahj.2013.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 3 biodegradable polymer and durable polymer-based drug-eluting stents in all-comers (BIO-RESORT): Rationale and study design of the randomized TWENTE III multicenter trial

Abstract: BIO-RESORT is a large, prospective, randomized, multicenter trial with three arms, comparing two DES with biodegradable coatings versus a reference DES with a durable coating in 3540 all-comers. The trial will provide novel insights into the clinical outcome of modern DES and will address the impact of known and so far undetected diabetes mellitus on post-PCI outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…In our study, the ongoing major bleeding risk during follow-up was substantially lower than that previously reported and was not significantly different among groups [26]. These results are similar to those of other recent DES registries in diabetics and do reassure regarding the ongoing bleeding risk in these patients treated with DAPT up to 1 year after PCI [4,14].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In our study, the ongoing major bleeding risk during follow-up was substantially lower than that previously reported and was not significantly different among groups [26]. These results are similar to those of other recent DES registries in diabetics and do reassure regarding the ongoing bleeding risk in these patients treated with DAPT up to 1 year after PCI [4,14].…”
Section: Discussionsupporting
confidence: 76%
“…This report presents the findings in the diabetic patient group enrolled in the e-SELECT registry, evaluating the interaction between baseline DM treatment (insulin use vs. no insulin) and outcome. Although first-generation SES have been replaced by newer stent designs eluting different antiproliferative drugs, a relatively large number of second-generation DES are still coated with sirolimus and are currently used in patients with DM [4]. Accordingly, the e-SELECT registry data may serve as a clinical benchmark for future comparative effectiveness analyses and may improve our clinical understanding of PCI long-term results in the DM population.…”
Section: Introductionmentioning
confidence: 99%
“…Five-year follow-up data comparing biodegradable polymer-based DES with durable polymer DES showed a safety benefit and a significant reduction in very late stent thrombosis [13]. The currently ongoing BIORESORT prospective randomized-controlled multicenter trial comparing biodegradable coating DES with permanent coating DES will also address long-term clinical follow-up [14]. In our randomized trial with 3 months of DAPT after BMS plus DCB, we found no definite stent thrombosis up to 5 years.…”
Section: Discussionmentioning
confidence: 79%
“…69, 71, 72 . Other strategies that are utilized in tissue engineering could also be helpful, including the patterning of scaffolds to induce and direct cell invasion 73 .…”
Section: Engineering Techniques For Harnessing Endogenous Mesenchymalmentioning
confidence: 99%